Nepal : Poverty Reduction Strategy Paper Annual Progress Report; Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report ;, 2006)
This note documents slow economic growth and significant delays in reform implementation owing to continued political instability and conflict. The annual progress report (APR) reviews progress in the power sector, but does not mention some critical challenges. It outlines some progress in public sector reforms and private sector development. The APR analyzes the impact on disadvantaged groups of several government of Nepal's programs, but recognizes a decrease in spending for targeted programs. Progress has been made in finalizing and launching of a framework for monitoring and evaluation.